Lactobacillus rhamnosus GG attenuates MASLD/MASH progression by modulating gut microbiota and metabolic pathways - Wang, Shi-Long; Liang, Si; Li, Si-Yu; Fu, Jin-Wen; Wang, Zi-Yi-Ru; Zhu, Dong-Qing; Chen, Nan (Frontiers in Microbiology, 2025)
IntroductionNon-alcoholic fatty liver disease (MASLD) is a common liver condition with a global prevalence of approximately 25%, often associated with overweight, obesity, and abnormalities in glucose and lipid metabolism. Its histological hallmark is hepatic steatosis. Non-alcoholic steatohepatitis (MASH), an advanced form of MASLD, can lead to cirrhosis and liver cancer. Dysbiosis of the gut microbiota plays a significant role in chronic liver diseases, making probiotic treatment a focal point in MASLD research. Studies have shown that Lactobacillus rhamnosus GG (LGG) can improve gut microbiota, reduce hepatic fat accumulation, and lower blood lipid levels in MASLD model mice. However, the role of LGG in the progression from MASLD to MASH remains unclear.MethodsIn this study, we constructed MASLD and MASH models using a high-fructose, high-fat diet combined with carbon tetrachloride (CCl4) induction to explore the effects of LGG on disease progression. Our findings revealed that in the MASLD model, LGG improved lipid metabolism and inflammatory responses by modulating the gut microbiota (e.g., increasing the abundance of Bacteroidetes) and promoting the production of short-chain fatty acids (SCFAs). Additionally, LGG reduced the expression of genes related to lipogenesis, further alleviating MASLD.ResultsIn the MASH model, LGG primarily exerted its effects by inhibiting the TGF-β/SMAD signaling pathway and reducing the expression of pro-inflammatory factors (e.g., IL-1β, IL-6, TNF-α), thereby mitigating liver fibrosis and inflammation. Furthermore, LGG restored intestinal barrier function, reduced intestinal permeability, and prevented harmful substances like endotoxins from entering the liver, further alleviating hepatic inflammation and fibrosis.DiscussionAlthough LGG shows promise in the treatment of MASLD and MASH, its mechanisms of action and long-term effects require further investigation. Future research should focus on optimizing the types, dosages, and treatment regimens of probiotics, as well as monitoring their long-term impact on gut microbiota balance, to ensure their safety and efficacy in clinical applications.